Persepsi Guru dan Peserta Didik Terhadap Tantangan Pemanfaatan Teknologi dalam Pembelajaran di Sekolah Dasar: Tinjauan Literatur - Dea Melfiana Putri; Arhaya Umil Azmah; Adrias Adrias; Fadila Suciana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study uses the Systematic Literature Review (SLR) approach which aims to examine how teachers and students view the challenges of using technology in elementary school learning. The purpose of this analysis is to provide insight to teachers and students to find out the various challenges that can be faced in the use of technology in the learning process. This literature review also provides knowledge about the challenges faced in the use of technology in learning in primary schools. The data in this study were taken from five journal articles relevant to the topic, published between 2021 and 2025. Data analysis uses content analysis techniques where each source or literature studied is adjusted to the context of the subject presented in this study. The results of this study show that the role of teachers is very important in the use of technology in learning. To improve the quality of learning, the perception of teachers and students is very important regarding the use of technology in this learning. In the use of technology, there are still a number of obstacles to integrating technology into the learning process. However, the existing challenges can be overcome with the right support from various parties.